Impact of uncertainties in wind and solar energy to the optimal operation of DG based on MCS - Eman Mahmoud; Salem Alkhalaf; Mahmoud Hemeida; Tomonobu Senjyu; Mahrous Ahmed; Ashraf M. Hemeida; Omar Abdel-Rahim (Ain Shams Engineering Journal, 2024)
Optimum operation of power system network becomes of great importance to handle the problem of power shortage. Connecting renewable energy (RE) based distributed generators (DG) into electrical networks (EN) are spreading rapidly to earn more benefits environmentally and economically. This paper aims to optimally operate DGs in order to minimize daily power loss in case of uncertainty of wind and PV system. Three different types of DGs, photovoltaic DG (PVDG), wind DG (WDG) and conventional DG (CDG) are connected to IEEE 33-bus system. Monte Carlo simulation (MCS) is used to generate probable scenarios for wind and photovoltaic power plants based on actual data for wind speed and solar radiation for one day. Fast forward scenario reduction (FFSR) is used to reduce the number of scenarios generated by MCS. Particle swarm optimization (PSO) is used to minimize daily power losses through determining the optimum operating point (operating power and power factor (PF)) for CDG to cope with PVDG and WDG uncertainties.